Entrepreneurial orientation, technological innovation, and SMEs performance during COVID-19: The role of adversity quotient - Achmadi Achmadi (Jurnal Riset Manajemen dan Bisnis, 2022)
Dynamic economic development and setbacks in various business sectors due to the COVID-19 pandemic have caused acute difficulties in almost all countries. However, the creative economy, which MSMEs dominate, has played an essential role in maintaining a sustainable economy due to the general decline in the global market. This study aims to develop a theoretical model to provide insights into the association between innovation practices and SMEs' performance and survival while underlining the auxiliary role of internal capabilities such as entrepreneurial orientation, technological innovation, and adversity queries (AQ). The literature review supports that EO, innovation, and AQ play a vital role in SMES business continuity, especially in unpredictable situations. EO and AQ as individual characteristics can be a strength for MSME owners to maintain their performance through innovation. This article postulates that AQ can impact SMEs' performance and strengthen the innovation-SMEs relationship